A comparative study between thermophilic and mesophilic membrane aerated biofilm reactors. Issue 2 (1st March 2007) - Liss, Steven N; ,
Abstract : The concept of thermophilic membrane aerated biofilm reactor (MABR) was investigated for the first time and examined for its potential to treat a high strength synthetic wastewater. Biofilms at 55 °C were successfully grown on gas permeable silicone hollow fiber membranes. At a feed chemical oxygen demand (COD) of 1200 mg/L and a reaction time of 1 d, COD removal efficiency (90%) of the thermophilic MABR (55 °C) was much higher than that (67%) of the mesophilic MABR operated at 18-28 °C. Biofilms in the thermophilic reactor were less thick, more hydrophobic, and less negatively charged. This study indicated that MABRs operated at thermophilic temperatures could be an effective means for controlling biofilm thickness and for the treatment of warm high strength organic waste.